La Naturaleza de la Ciencia y la Tecnología. Una experiencia para desarrollar el Pensamiento Crítico - Ortega-Quevedo, Vanessa; Gil Puente, Cristina (Revista Científica, 2019)
The main objective of the research presented is the development of Critical Thinking (CT) of Primary Education students and the teaching of topics related to the Nature of Science and Technology (NoS&T). A Teaching-Learning Sequence is developed and implemented, both the analysis and the evaluation of the results obtained is done through a quantitative approach. The study is carried out with a sample of 130 participants of the 6th grade of Elementary Education. The evaluation instruments that used are two adaptations, the first is the Opinion Questionnaire on Science, Technology, and Society, and the second is a Spanish version of the Halpern test. As a result, we observed that the participants in the study show significant improvements in PC skills and conceptions related to the NoS&T studied. Consequently, experience is considered successful.